ANTIBACTERIAL ACTIVITY OF CAULERPA RACEMOSA ENDOPHYTIC FUNGI FROM LEMUKUTAN ISLAND WATERS - Melia Trianasta; Warsidah; Nurdiansyah, Syarif Irwan; Sofiana, Mega Sj; Hidayat, Maulana (Hasanuddin University, 2021)
Green macroalgae Caulerpa racemosa from the waters of Lemukutan Island was isolated to obtain endophytic fungi. Endophytic fungi were explored to determine the antibacterial activity. Isolation of endophyte fungi was carried out by dilution method using PDA (Potato Dextrose Agar) seawater media. Endophyte fungi with different morphology were obtained 11 isolates, namely CRF01, CRF02, CRF03, CRF04, CRF05, CRF06, CRF07, CRF08, CRF09, CRF10 and CRF11. Antibacterial activity testing was carried out by agar diffusion method. Endophyte fungi isolate CRF09 showed the highest activity against both Escherichia coli and Staphylococcus aureus test bacteria with inhibition zone diameters of 15.96 mm and 16.47 mm respectively. Endophyte fungi isolates identified from the green macroalgae Caulerpa recemosa were of the genus Trichocladium sp., Aspergilus sp., Chaetomium sp., Coprinus sp., Hymenochaete sp., Rhizopus sp., Trenella sp. and Zygorhynchus sp. Keywords: antibacterial. endophyte fungi, Caulerpa racemosa, Lemukutan Island, activity